A Follow-Up Study On Drug Addicts After Treatment And Rehabilitation. - Navaratnam, V.; Foong Kin, Foong Kin (Pusat Penyelidikan Dadah Kebangsaan, Universiti Sains Malaysia, 1996)
This is a prospective six months follow up study on drug addicts after treatment and rehabilitation. The main concern is to find out during this critical period, whether the addicts were able to stay off drugs or fall back to drugs and what happened during the process.